Rediscovery Of The Missing Syntypes Of Mabuya Nagarjuni Sharma 1969 (Reptilia : Scincidae) In The Collection Of The Zoological Survey Of India - Das, Indraneil; Srinivasulu, C. (Bombay Natural History Society (BNHS), 2007)
Sharma (1969) described Mabuya nagarjuni based on specimens collected from Vijaypuri South, Andhra Pradesh, near the right-bank of the River Krishna, 16º35' N, 79º28' E, ca. 152 m above msl. The original description did not formally designate a holotype, for which reason, all four specimens from the original type series need to be considered syntypes. The type series, which was collected on August 23, 1962 by B. Nath and I.N. Maligi, was deposited in the collection of the Zoological Survey of India (ZSI), Kolkata. This nominal species, along with other Asian members of the Scincidae once assigned to the genus Mabuya, was transferred to the genus Eutropis, in support of long-separated evolutionary lineages, representing distinct monophyletic radiations of the South American, Asian, Afro-Madagasy and Cape Verdian groups (Mausfeld et al. 2002), and the new name combination should be Eutropis nagarjuni (Sharma 1969).